Integrating anatomical and functional imaging for the assessment of coronary artery disease. (October 2013) - Lee, Andrea KY; Qutub, Mohammed A; Aljizeeri, Ahmed; Chow, Benjamin JW
Coronary artery disease (CAD) is a leading cause of morbidity and mortality. Invasive cardiac angiography with fractional flow reserve measurement allows for the anatomical and functional assessment of CAD. Given the invasive nature of invasive cardiac angiography and the risks of procedure-related complications, research has focused upon noninvasive methods for anatomical and functional measures of CAD. As such, there is growing interest in the development of hybrid imaging because it may provide incremental diagnostic information over each imaging modality alone. We will provide an overview of the evidence to date on the anatomical and functional stratification of CAD and current hybrid techniques.